2008
DOI: 10.1097/01.aids.0000327618.01362.6a
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders' opinions and expectations of the Global Fund and their potential economic implications

Abstract: Objective To analyze stakeholder opinions and expectations of the Global Fund to Fight AIDS, Tuberculosis, and Malaria, and to discuss their potential economic and financial implications. Design The Global Fund commissioned an independent study, the “360° Stakeholder Assessment,” to canvas feedback on the organization’s reputation and performance with an on-line survey of 909 respondents representing major stakeholders worldwide. We created a proxy for expectations based on categorical responses for specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Seven of the quantitative studies were descriptive and did not use any explicit statistical methods to analyse their data. The remaining nine quantitative studies used a variety of study designs: one study was an uncontrolled before–after study, 23 one uncontrolled study reported data before and during implementation, 24 one study utilized time-series data, 25 two were cohort studies, 26 , 27 two were cross-sectional studies, 28 , 29 one study used Global Fund grant data for modelling 30 and one study modelled economic costs of a national insecticide-treated bed net (ITN) voucher scheme. 31 Only one of the six qualitative studies used an explicitly defined qualitative method of analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven of the quantitative studies were descriptive and did not use any explicit statistical methods to analyse their data. The remaining nine quantitative studies used a variety of study designs: one study was an uncontrolled before–after study, 23 one uncontrolled study reported data before and during implementation, 24 one study utilized time-series data, 25 two were cohort studies, 26 , 27 two were cross-sectional studies, 28 , 29 one study used Global Fund grant data for modelling 30 and one study modelled economic costs of a national insecticide-treated bed net (ITN) voucher scheme. 31 Only one of the six qualitative studies used an explicitly defined qualitative method of analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies did not target a specific disease, but were addressing wider issues such as countries’ absorptive capacity, 30 Global Fund's performance-based funding approach, 40 Global Fund-supported programmes’ contribution to international health targets, 41 an innovative financing scheme used by the Global Fund (Debt2Health Conversion Scheme) 37 or analysing stakeholder opinions and expectations using the Global Fund 360° Stakeholder Survey. 29 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations